Massive and efficient encapsulation of single cells in monodisperse droplets and collagen–alginate microgels using a microfluidic device - Liu, Dan; Xuanyuan, Tingting; Liu, Xufang; Fu, Wenzhu; Liu, Wenming (Frontiers in Bioengineering and Biotechnology, 2023)
Single-cell manipulation is the key foundation of life exploration at individual cell resolution. Constructing easy-to-use, high-throughput, and biomimetic manipulative tools for efficient single-cell operation is quite necessary. In this study, a facile and efficient encapsulation of single cells relying on the massive and controllable production of droplets and collagen–alginate microgels using a microfluidic device is presented. High monodispersity and geometric homogeneity of both droplet and microgel generation were experimentally demonstrated based on the well-investigated microfluidic fabricating procedure. The reliability of the microfluidic platform for controllable, high-throughput, and improved single-cell encapsulation in monodisperse droplets and microgels was also confirmed. A single-cell encapsulation rate of up to 33.6% was achieved based on the established microfluidic operation. The introduction of stromal material in droplets/microgels for encapsulation provided single cells an in vivo simulated microenvironment. The single-cell operation achievement offers a methodological approach for developing simple and miniaturized devices to perform single-cell manipulation and analysis in a high-throughput and microenvironment-biomimetic manner. We believe that it holds great potential for applications in precision medicine, cell microengineering, drug discovery, and biosensing.